In Vitro Antioxidant, Antithrombotic and Anti-Inflammatory Properties of the Amphiphilic Bioactives from Greek Organic Starking Apple Juice and Its By-Products (Apple Pomace) - Maria Vandorou; Christos Plakidis; Ilektra Maria Tsompanidou; Anna Ofrydopoulou; Katie Shiels; Sushanta Kumar Saha; Alexandros Tsoupras (Applied Sciences)
The anti-inflammatory, antithrombotic and antioxidant effects of extracts from both apple juice and apple by-products (apple pomace) of organic cultured Greek Starking apples were evaluated in vitro. All extracts were separated in their total amphiphilic compounds (TACs) and total lipophilic compounds (TLCs) and assessed for their total phenolic content (TPC), total carotenoid content (TCC) and antioxidant activities (by the DPPH, ABTS and FRAP assays), as well as for their anti-inflammatory potency against the thrombo-inflammatory mediator, platelet activating factor (PAF) and their antithrombotic effects against a standard platelet-agonist (ADP) in human platelets. The rich-in-TAC extracts showed much higher content in phenolics and carotenoids than the TLC extracts, which was also reflected by the much stronger antioxidant capacities observed in TAC. ATR-FTIR spectroscopy revealed the presence not only of phenolics and carotenoids but also of amphiphilic polar lipids (PLs) in TAC, the structural analysis of which with LC–MS further revealed a fatty acid composition favorable for unsaturated fatty acids (UFAs) versus saturated ones (SFAs). The presence of such bioactive PLs that are rich in UFA within the TAC extracts of apple juice and apple pomace provide an explanation for the observed potent anti-inflammatory effects and antithrombotic properties of these extracts, mainly against the inflammatory pathway of PAF but also against platelet aggregation induced by ADP. Overall, these results further support the antioxidant, antithrombotic and anti-inflammatory potential of rich-in-TAC extracts from organic cultured apples and especially from their apple pomace by-products, which can further be utilized as sustainable bioactive ingredients in several functional products in a circular economy design.